A child with atopic features, raised serum IgE, and recurrent infection treated with levamisole. Issue 1 (January 1981) - Businco, L; Laurenti, F; Rossi, P; Galli, E; Aiuti, F
Abstract : A 6-year-old girl had a long history of severe eczema, asthma, recurrent otitis media, and staphylococcal infections with disseminated chronic skin abscesses. Immunological studies showed a neutrophil chemotaxis defect, hyperimmunoglobulinaemia E, IgE antibodies against cows' milk proteins, absence of IgM, and absence of staphylococcal haemolysins. Neutrophil phagocytic and bactericidal functions and complement system were normal. In the course of treatment with levamisole (2.5 mg/kg, 3 times a week for one year) a striking clinical improvement occurred: the skin lesions and the staphylococcal abscesses gradually cleared and the girl gained weight. There was also a partial correction of the immune deficiency.